Europe's Century of Crises Under Dollar Hegemony - Brown, Brendan. author. aut Link
XV, 233 p.
Keywords: This book showcases written dialogue from Brendan Brown and Philippe Simonnot on the subject of European monetary turmoil past and present and what hope there could be for future reform. Starting with the collapse of the gold standard in 1914, proceeding to the brief gold-dollar standard of the mid inter-war years, on to the collapse of Bretton Woods and the heyday of the Deutsche mark and ultimately discussing the euro, this book looks at a broad range of financial history alongside many new and provoking hypotheses about the devastating monetary turbulence of the successive eras, always with a focus on the US monetary hegemon. A highlight of the dialogue is an exploration of how past and future crises could combine to give birth to sound money in Europe – the launch, in effect, of a new euro. In the questions and answers within these pages, the authors draw on global examples and the challenges for Europe in deciding how to adapt to successive monetary shocks from the US, crafting a book that would be of interest to general finance and economics readers alongside students, researchers, and policymakers. .